Social group and health-care provider interventions to increase the demand for malaria rapid diagnostic tests among community members in Ebonyi state, Nigeria: a cluster-randomised controlled trial. Issue 3 (March 2021) - Omale, Ugwu I; Azuogu, Benedict N; Alo, Chihurumnanya; Madubueze, Ugochukwu C; Oka, Onyinyechukwu U; Okeke, Kingsley C; Okafor, Ifeyinwa M; Utulu, Rowland; Eze, Irene I; Akpan, Uduak E; Iloke, Chijioke V; Nnubia, Anthonia O; et al.
Summary: Background: The rate of diagnostic testing for malaria is still very low in Nigeria despite the scale-up of malaria rapid diagnostic test (MRDT) availability, following WHO's recommendation of universal diagnostic testing in 2010. We investigated whether a social group sensitisation and education intervention (social group intervention) and a social group intervention plus health-care provider training intervention would increase the demand (use or request, or both) for MRDTs among community members in Ebonyi state, Nigeria. Methods: We did a three-arm, parallel, open-label, stratified cluster-randomised controlled trial in Ebonyi state, Nigeria, to evaluate the effects of two interventions compared with a control. We randomly assigned geographical clusters that were accessible (close to a road that was drivable even during the rainy seasons) and had at least one eligible public primary health facility and patent medicine vendor (those that offered MRDT services) in a 1:1:1 allocation to the control arm (receiving no intervention), social group arm (receiving sensitisation and education about MRDT), or social group plus provider arm (receiving the social group intervention plus provider training in health communication about MRDT). Investigators, participants (social groups, providers, respondents), and interviewers could not be masked to group assignments. The primary outcome was the proportion of children younger than 5 years with fever or malaria-like illness, in the 2 weeks preceding a household survey, who received an MRDT, and the coprimary outcome was the same outcome but among children aged 5 years and older (ie, up to and including 17 years) and adults (excluding pregnant women). The outcomes were measured at an individual level via household surveys before the interventions and 3 months after the end of the interventions. All analyses were done using a cluster-level method on an intention-to-treat basis. This trial is registered with ISRCTN, number ISRCTN14046444. Findings: We carried out eligibility screening and recruitment of participants (clusters, social groups, and providers) between July 2 and Sept 27, 2018. 34 clusters met the eligibility criteria and 18 were randomly selected to participate and randomly assigned to arms (six clusters per arm). A mean proportion of 40·6% (SD 14·5) of eligible children younger than 5 years in the control arm received an MRDT, versus 66·7% (11·7) in the social group arm (adjusted risk difference [aRD] 28·8%, 95% CI 21·9–35·7, p<0·0001) and 71·7% (19·8) in the social group plus provider arm (aRD 32·7%, 24·9–40·5, p<0·0001), with no significant difference between the social group arm and the social group plus provider arm. A mean proportion of 36·3% (18·5) of eligible children aged 5 years and older in the control arm received an MRDT, versus 60·7% (14·0) in the social group arm (aRD 25·6%, 16·8–34·4, p=0·0004), and 59·5% (18·3) in the social group plus provider arm (aRD 28·0%, 19·5–36·5, p=0·0002), with no significant difference between the social group arm and the social group plus provider arm. Interpretation: The sensitisation and education of social groups about MRDTs can significantly increase the demand for MRDTs. This intervention is pragmatic and could be applied within malaria control or elimination programmes, in Nigeria and in other high-burden countries, to enhance diagnostic testing for patients suspected of having malaria. Funding: There was no funding source for this study.